Preparing students for diverse careers: Developing career literacy with final-year writing students - Bennett, Dawn; Robertson, Rachel (University of Wollongong, 2015)
Graduates from generalist science and arts degrees can face diverse careers characterised by portfolios of simultaneous, self-managed roles. This paper reports from a study on identity and career literacy in which final-year professional writing and publishing students developed an ePortfolio and engaged in open blogging during their industry internships. The ePortfolio emerged as a vehicle through which identity was challenged and negotiated with educator and peer support. However, students engaged only when the ePortfolio was mandated, and deep engagement was the result of the ePortfolio being presented as a practical career development tool. Findings suggest that the combination of ePortfolio and internship is an effective strategy for developing the career literacy needed for the transition to graduate life.